Carbon Dioxide as Mediating Compound Between Organic and Inorganic Matter - Armin Reller (CHIMIA)
The role of carbon dioxide within the natural cycles of matter and energy is shortly discussed. Possibilities for the generation of organic carbon compounds by the catalyzed reaction of molecular hydrogen with natural metal carbonates are displayed. Together with the exothermal recarbonatization of the so-formed metal oxides, a closed cycle for conversions of organic and inorganic carbon compounds is obtained, within which no fossil carbonaceous matter takes part.